Intelligence and Security Informatics Pacific Asia Workshop, PAISI 2011, Beijing, China, July 9, 2011. Proceedings - Chau, Michael; Wang, G. Alan.; Zheng, Xiaolong; Chen, Hsinchun; Zeng, Daniel; Mao, Wenji; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Pacific Asia Workshop on Intelligence and Security Informatics, PAISI 2011, held in Beijing, China, in July 2011. The 8 revised full papers and the 5 short papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on terrorism informatics and crime analysis; intelligence analysis and knowledge discovery; information access and security; and infectious disease informatics.
Keywords: Computer science; Computer Communication Networks; Data mining; Information systems; Computers -- Law and legislation; Information Systems; Computer Science; Information Systems Applications (incl.Internet).; Data Mining and Knowledge Discovery; Computer Communication Networks; Computers and Society; Legal Aspects of Computing; Management of Computing and Information Systems